Implikasi Kebijakan Pendidikan Profesi Guru (PPG) Terhadap Peningkatan Kompetensi Guru - Yusminingsih (Aafiyah: Jurnal Multidisiplin Ilmu, 2025)
This study examines the implications of the Teacher Professional Education (PPG) policy on improving teacher competence through a library research approach. By analyzing scientific literature, legal frameworks, academic journals, and officially published government documents, this research provides a comprehensive understanding of how PPG is designed and implemented as a strategic national effort to strengthen the four core competencies of teachers: pedagogical, professional, personal, and social. The findings show that PPG significantly contributes to enhancing teachers’ competencies, especially through structured mechanisms such as lesson study, contextual material mastery, and reflective teaching practices. However, the effectiveness of the policy is also influenced by various supporting and inhibiting factors, including institutional commitment, facilitators’ quality, administrative burdens, and limitations in translating theoretical mastery into daily classroom practice. This study highlights the need for a more sustainable post-PPG mentoring system to ensure long-term competency development and alignment with real educational challenges. Thus, PPG is both a transformative and necessary policy to elevate national education quality through professionalized teaching.